MORPHOLOGICAL ANALYSIS OF LEAF EPIDEMIS AND POLLEN IN JATROPHA SPECIES FROM NIGERIA - Soyewo, Luke Temitope; Adegbola, G. A.; Odewo, S. A.; Adeniji, K. A.; Oyebola, T. O.; Ajani, B. A. (FUDMA Journal of Sciences, 2024)
The genus Jatropha was investigated through epidermal cell and pollen morphology to enhance species identification beyond conventional floral and vegetative characteristics. Four species of Jatropha in Nigeria was put into considerations on this study (Jatropha curcas, Jatropha multifida, Jatropha. podagrica, and Jatropha. gossypifolia). All species examined exhibited paracytic stomata confined to the adaxial leaf surface, with the abaxial side being devoid of stomata or trichomes. Among the studied species, Jatropha. multifida displayed the largest stomatal length (27.5 µm) and width (17.5 µm), whereas Jatropha. curcas, Jatropha. podagrica, and Jatropha. gossypifolia showed stomatal lengths ranging from 15.0 µm to widths of 12.5 µm. The anticlinal cell walls were generally straight to curve across all species. Pollen grains in the genus were predominantly large, with an exine pattern characteristic of the Croton subfamily. Jatropha. multifida had the smallest gemmae size (2.50 µm) and exhibited the lowest polar axis (52.1 µm) and equatorial diameter (51.6 µm) measurements. These findings suggest that Jatropha species may be highly susceptible to environmental influences, with morphological traits, such as epidermal and pollen structures, varying significantly depending on growth conditions. Environmental factors like temperature, humidity, and soil quality likely impact the development of these traits, leading to observable differences between species. This highlights the value of using epidermal and pollen morphology to distinguish Jatropha species. However, the results also underscore the need for further research on genetic expression to understand the genetic mechanisms driving species variability. A deeper understanding of these mechanisms would improve species identification and support...
Keywords: Jatropha; Morphology; Abaxial; Anticlinal; Paracytic